Methods for Calculating Activation Energy for Portland Cement - Poole, Jonathan L.; Riding, Kyle A.; Folliard, Kevin J.; Juenger, Maria C. G.; Schindler, Anton K. (My University, 2010)
The accurate prediction of thermal gradients in concrete calls for models that characterize the temperature sensitivity of the hydration of cementitious materials. The most common method used for this purpose is the Arrhenius equation, which requires the selection of an activation energy Ea to define the temperature sensitivity of the reaction. For cementitious materials, Ea is typically computed using either isothermal calorimetry or compressive strength data. There is disagreement in literature as to the proper method to determine Ea. The Ea of different cementitious pastes was determined from isothermal calorimeter results using three different computational methods. The results were used to develop a systematic computational method for characterizing Ea to account for the effect of temperature on the overall rate of hydration of cementitious materials. This work lays the groundwork for more extensive studies to determine the effect of a wide variety of variables on Ea.
Keywords: Calorimeter; Hydration; Portland cement